(untitled) (Biological Sciences - PJSIR, 2005)
The lipolytic activities of lipases lip-I, lip-II and lip-III, purified from rice bran variety Paijam, were investigated after physical and chemical treatments. The purified lipases had pH optima of 7.3-8.0 and temperature optima of 34-40 °C. The results indicated that lip-I was more stable than lip-II and lip-III. The lipases isolated from rice bran, variety Paijam, belong to the category of alkaline lipases. Bile salts were found to be weak activators for the activation of lipases, while maximum activities were obtained with deoxycholate. The activities of rice bran lipases were enhanced by the presence of Ca++ upto certain concentrations, while EDTA application strongly inhibited the lipolytic activities. Rice bran lipases were more sensitive to the denaturing agent guanidine-HCl than urea. The presence of heavy metal ions, such as Cu++, Hg++, Zn++, Fe++, strongly inhibited activities of the lipases, while such metals as Ba++, Mg++ and Mn++ slightly increased the activities of lipases.